Immunohistochemical study suggesting a complementary role of kallikreins hK2 and hK3 (prostate-specific antigen) in the functional analysis of human prostate tumors. - Tremblay, R. R. (1997)
The development of monoclonal antibodies directed against prostatic kallikrein hK2 prompted us to evaluate its content, along with that of hK3 (prostate-specific antigen), in human prostate carcinoma. Seventy tumors categorized according to the M.D. Anderson Hospital classification (grade I to IV) were analyzed by immunohistochemistry. The staining intensity or the kallikrein content of benign prostatic hyperplasia glandular tissue (used as control) and of grade I tumors appeared similar. In grade II to IV tumors, histochemical data revealed highly variable hK2 or hK3 content in approximately 25% of tumors. Such patterns are consistent with a current observation related to heterogeneity of prostate tumors. In addition, a few tumors did not express hK3 (n = 3), hK2 (n = 3), or both (n = 3), indicating that some growth patterns of prostatic neoplasia are associated with a lack of secretion or storage of hK3 or hK2 for immunodetection. This statement also appears relevant to metastases. It was interesting to note that 4% of hK3-negative tumors had detectable hK2. Because of the importance of hK3 as a serum marker of prostate disorder, this study addresses for the first time the question of the relative importance of both hK3 and hK2 in the immunohistochemical diagnosis of prostatic tumors. We conclude that hK2 may add new information to prostate cancer diagnosis and characterization.